Conformation Control of Iminodibenzyl-Based Thermally Activated Delayed Fluorescence Material by Tilted Face-to-Face Alignment With Optimal Distance (tFFO) Design - Kusakabe, Yu; Wada, Yoshimasa; Nakagawa, Hiromichi; Shizu, Katsuyuki; Kaji, Hironori (Frontiers in Chemistry, 2020)
In organic light emitting diodes (OLEDs), all triplet excitons can be harvested as light via reverse intersystem crossing (RISC) based on thermally activated delayed fluorescence (TADF) emitters. To realize efficient TADF, RISC should be fast. Thus, to accomplish rapid RISC, in the present study, a novel TADF emitter, namely TpIBT-tFFO, was reported. TpIBT-tFFO was compared with IB-TRZ, which contains the same electron donor and acceptor segments, specifically iminodibenzyl and triazine moieties. TpIBT-tFFO is based on a recently proposed molecular design strategy called tilted face-to-face alignment with optimal distance (tFFO), whereas IB-TRZ is a conventional through-bond type molecule. According to quantum chemical calculations, a very large RISC rate constant, kRISC, was expected for TpIBT-tFFO, because not only the lowest triplet state but also the second lowest triplet state were close to the lowest excited singlet state, as designed in the tFFO strategy. IB-TRZ has two different conformers, leading to dual emission. Conversely, owing to excellent packing, the conformation was fixed to one in the tFFO system, resulting in single-peaked emission for TpIBT-tFFO. TpIBT-tFFO displayed TADF-type behavior and afforded higher photoluminescence quantum yield (PLQY) compared to IB-TRZ. The kRISC of TpIBT-tFFO was determined at 6.9 ×106 s−1, which is one of the highest values among molecules composed of only H, C, and N atoms. The external quantum efficiency of the TpIBT-tFFO-based OLED was much higher than that of the IB-TRZ-based one. The present study confirms the effectiveness of the tFFO design to realize rapid RISC. The tFFO-based emitters were found to exhibit an additional feature, enabling the control of the molecular conformations of the donor and/or acceptor segments.